0
$\begingroup$

does anybody know how to take a second order transfer function with no zeros (no s terms in the numerator):

$$ g(s) = K\frac{\omega_n^2}{s^2 + 2\zeta \omega_n s + \omega_n^2} $$

and represent it using two first order transfer functions.

the layout for my second order transfer function is

     (number)/((number)s^2 + (number)s + (number))

this second order transfer function was previously in the form

(number)/((number) s + (number))^2 before i expanded the brackets

$\endgroup$
2
  • $\begingroup$ Not clear, you want to represent G(s) by 2 1st-order transfer function having the same denominator ? $\endgroup$ – Ben Mar 22 at 19:12
  • $\begingroup$ and generally, you simply need to factorize the polynomial. $$ \frac{-b± \sqrt{b^2-4ac}}{2a}$$ $\endgroup$ – Ben Mar 22 at 19:13
1
$\begingroup$

For $|\zeta| \le 1$, let $\zeta= \cos\theta$, so $\theta=\mathrm{arccos}\,\zeta$

$$\begin{align*}g(s) &= K\frac{\omega_n^2}{s^2 + 2\zeta \omega_n s + \omega_n^2}\\ \\ &= K\frac{\omega_n^2}{s^2 + 2\omega_n s \cos\theta+ \omega_n^2(\cos^2\theta +\sin^2\theta)}\\ \\ &= K\frac{\omega_n^2}{(s + \omega_n \cos\theta)^2+ \omega_n^2\sin^2\theta}\\ \\ &= \sqrt{K}\frac{\omega_n}{s + \omega_n \cos\theta + j\omega_n\sin\theta} \cdot \sqrt{K}\frac{\omega_n}{s + \omega_n \cos\theta -j\omega_n\sin\theta} \\ \\ &= \sqrt{K}\frac{\omega_n}{s + \omega_n e^{j\theta}} \cdot \sqrt{K}\frac{\omega_n}{s + \omega_n e^{-j\theta}} \\ \\ \end{align*}$$

For $|\zeta| \ge 1$, since $\cosh\theta \ge 1$, let $\zeta= \pm\cosh\theta$, so $\theta=\mathrm{acosh}\,\left(\pm\zeta\right)$

$$\begin{align*}g(s) &= K\frac{\omega_n^2}{s^2 + 2\zeta \omega_n s + \omega_n^2}\\ \\ &= K\frac{\omega_n^2}{s^2 \pm 2\omega_n s \cosh\theta+ \omega_n^2(\cosh^2\theta -\sinh^2\theta)}\\ \\ &= K\frac{\omega_n^2}{(s \pm \omega_n \cosh\theta)^2- \omega_n^2\sinh^2\theta}\\ \\ &= \sqrt{K}\frac{\omega_n}{s \pm \omega_n \cosh\theta + \omega_n\sinh\theta} \cdot \sqrt{K}\frac{\omega_n}{s \pm \omega_n \cosh\theta -\omega_n\sinh\theta} \\ \\ &= \sqrt{K}\frac{\omega_n}{s \pm \omega_n e^{\theta}} \cdot \sqrt{K}\frac{\omega_n}{s \pm \omega_n e^{-\theta}} \\ \\ \end{align*}$$

$\endgroup$
2
  • $\begingroup$ You assume that the poles are complex. There's the second case there the poles are real. $\endgroup$ – Ben Apr 2 at 11:30
  • 1
    $\begingroup$ @Ben Yeah, I made the assumption that $\xi \in [-1,1]$. $\xi = \pm \cosh \theta$ could be used for $\xi$ not in that range. $\endgroup$ – Andy Walls Apr 3 at 1:44
0
$\begingroup$

The roots of the quadratic equation $s^2 + 2\xi \omega_n + \omega_n^2=0$ are $s_{1,2} = -\xi w_n \pm \omega_n \sqrt{\xi^2 - 1} = -\xi w_n \pm i\omega_n \sqrt{1 - \xi^2}$ where we define the damping frequency $\omega_d = \omega_n \sqrt{1 - \xi^2}$ when $\xi < 1$. Therefore, the usual second order transfer function $\frac{\omega_n^2}{s^2 + 2\xi \omega_n + \omega_n^2=0} = \frac{\omega_n}{s-(-\xi w_n + i \omega_d)} \cdot \frac{\omega_n}{s-(-\xi w_n - i \omega_d)}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.